Engineering And Application Of Vibration System Granulator Machine For Processing Organic Waste Into Compost In Gondangrawe Village Livestock Farmer Group Boyolali - Budi Kristiawan; Doddy Setiawan; Musabbikhah Musabbikhah (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT Compost production by partners in Gondangrawe Village, Boyolali, is still conventional with a capacity of 100 kg/month, low quality, and inconsistent. The objective of this community service project is to design and implement a vibration system granulator machine to process organic waste, in order to improve production efficiency, quality, and the economic value of compost. The implementation method includes engineering design validated through Finite Element Analysis (FEA), manufacturing, as well as intensive training and assistance to KTTSR related to operations and packaging. The results of this community service project are the implementation of a granulator machine unit that has been proven to be safe (Safety Factor 15.00) and economically feasible. The application of this technology has successfully increased production capacity to 160 kg/month (8 hours of operation) and produced more uniform compost granules, thereby facilitating measurement and increasing sales value. Keywords: Granulator Machine, Organic Fertilizer, Organic Waste